2015
DOI: 10.1021/acs.jpclett.5b02220
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Electrochemical Trapping of Carbon Dioxide Using 4,4′-Bipyridine That Does Not Require Thermal Activation

Abstract: Sequestering carbon dioxide emissions by the trap and release of CO2 via thermally activated chemical reactions has proven problematic because of the energetic requirements of the release reactions. Here we demonstrate trap and release of carbon dioxide using electrochemical activation, where the reactions in both directions are exergonic and proceed rapidly with low activation barriers. One-electron reduction of 4,4'-bipyridine forms the radical anion, which undergoes rapid covalent bond formation with carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 21 publications
1
86
0
Order By: Relevance
“…Since then, a number of systems have been developed for transporting chemical species by redox-active carriers that are activated at one electrode, to bind with the target species, and deactivated at the opposite electrode, to release the target and regenerate the carrier. 15,16 Systems that have been proposed for the concentration of CO 2 through this approach have been based on a number of different carrier molecules, such as quinones, [17][18][19][20] 4,4 0 -bipyridine, 21 and thiolates. 22,23 Quinones are of particular interest to this work for their superior electrochemical performance, serving as redox-active carriers for CO 2 in electrochemically mediated separation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of systems have been developed for transporting chemical species by redox-active carriers that are activated at one electrode, to bind with the target species, and deactivated at the opposite electrode, to release the target and regenerate the carrier. 15,16 Systems that have been proposed for the concentration of CO 2 through this approach have been based on a number of different carrier molecules, such as quinones, [17][18][19][20] 4,4 0 -bipyridine, 21 and thiolates. 22,23 Quinones are of particular interest to this work for their superior electrochemical performance, serving as redox-active carriers for CO 2 in electrochemically mediated separation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 4,4′-bipyridine (bipy) with delocalized -electrons of the pyridyl rings obtains increasing attention in preparing light emitting complexes in different technical applications, such as emitting materials for organic light emitting diodes, sensitizers in solar energy conversion, chemical sensors and so forth [6][7][8][9]. The ability of bipy to act as a rigid, rod-like organic building block in the self-assembly of coordination frameworks is well-known, such as, acting as a charge-compensating cation, a pillar bonding to inorganic skeletal backbone, an uncoordinated guest molecule and organic template, a bridge connecting two metal complex moieties, or linking a metal and an inorganic framework [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Quantum calculations suggested that the one electron oxidation of this adduct resulted in an extremely rapid dissociation, producing Bipy and CO 2 with a rate constant of 1.4 × 10 10 s À 1 . The reverse of reaction 3e refers to the electrochemical one electron oxidation of the Mebipy-CO 2 À adduct to give what is likely a transient radical intermediate, Mebipy-CO 2 , followed by dissociation of this species to give Mebipy and CO 2 , reaction 3c.…”
Section: Resultsmentioning
confidence: 99%